The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Political Science
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

The World-Historical Origins of Pan-Islamic Nationalism in Iran - Araghi, Farshad (2003)
In examining the world-historical context of the rise of pan-Islamic nationalism in Iran, this paper posits Islamic fundamentalism as a modern and global (rather than premodern and local) movement. Drawing on Polanyi and linking economy, polity, and culture, this study traces the origins of pan-Islamic nationalism in Iran to the transformation of the world-market relations in the second half of the nineteenth century and the rise of the food/agrarian regime after 1870. It shows that the relations of the state and the mercantile classes with the world market led to conflicting developments, viz., the national "contraction" of the state on the one hand and the international "expansion" of commercial classes on the other hand. The latter, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European expansion in the "Islamic world." Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for the struggle for the nationalization of the state. Hence, as a historical form, modernity and nationalism in the late nineteenth century Iran took a nonsecular character. Later, the Cold War politics revivified the pan-Islamic component of Iranian nationalism, creating the context for the rise to power of fundamentalism in the 1980s. The paper warns against the reification of place and culture rooted in binary conceptualizations of the local and the global phenomena.
Sociology
Keywords: Iran; Islam; Islamic fundamentalism; culture; fundamentalism; market; nationalism; pan-Islamism; protestant fundamentalism; religion; religious fundamentalism; world; world-market relations

Labor Organizing and Neoliberal Politics - Rudy, Preston (2003)
Neo-liberal policies and practices which impugn state policies as artificial interferences in the smooth operation of markets are at work globally, nationally and locally. Based on research about the Justice for Janitors in California, this paper examines the experience of the campaigns in San Jose and Sacramento. The paper is organized around a tension between two issues about markets that are explained by Karl Polanyi: their social reality as complex political constructions and the ideological justification for disembedding markets, aka the "Liberal Creed". In both campaigns the Justice for Janitors exposed the embeddedness of employers. On the other hand, in the ideological construction of their campaigns, the Justice for Janitors have not clearly confronted the "liberal creed" that justifies neo-liberal market practices. The JfJ campaigns have been successful at creating accountability for employers and politicians by revealing the concrete social relations within which markets are embedded, though they have largely failed to articulate an oppositional ideology to the liberal creed. At a minimum confronting this creed would place the state as central to the construction of market practices. The successes at instituting accountability of employers to democratic communities and the centrality of the state in securing that accountability will be undermined unless JfJ exposes the flaws of the liberal creed and clearly explains the importance of the state in securing the justice they seek.
Sociology
Keywords: United States; ideology; labor; labour; liberal creed; liberalism; markets; neoliberalism; political planning